Cardiovascular risk factors and glucose tolerance in midlife and risk of cognitive disorders in old age up to a 49-year follow-up of the Helsinki businessmen study. (18th August 2017) - Rantanen, Kirsi; Strandberg, Arto Y.; Salomaa, Veikko; Pitkälä, Kaisu; Tilvis, Reijo S.; Tienari, Pentti; Strandberg, Timo
Abstract: Purpose: The purpose of this study is to compare midlife predictors of old age dementia with or without concomitant atherosclerotic cardiovascular disease (ASCVD). Design: In the Helsinki Businessmen Study (men born in 1919–1934, n = 3309), death certificates (n = 1885) during up to 49-year follow-up (through 31 December 2013) were screened for dementia (n = 365) and ASCVD, and categorized as (1) AD without ASCVD ("pure" AD, n = 93), (2) AD + ASCVD (n = 126), (3) vascular dementia (VD, n = 82), (4) other or undefined etiology (n = 64). Using Cox analyses, death without dementia and dementia types were compared for the prediction by midlife ASCVD risk factors. Men without diagnosed dementia during follow-up were used as reference. Results: ASCVD risk factors predicted death without dementia during follow-up. Midlife cholesterol was higher in AD + ASCVD and VD as compared with men surviving to old age without known dementia. None of the midlife factors including cholesterol and glucose tolerance predicted pure AD, but midlife cholesterol predicted AD + ASCVD, both as a continuous (hazard ratio [HR] per SD 1.24, 95% CI, 1.04–1.47), and dichotomous variable (cutpoint 6.5 mmol/L; HR 1.67, 95% CI, 1.16–2.40). Conclusion: Midlife cholesterol predicted dementia with vascular features, but midlife vascular risk factors and glucose intolerance were not related to pure Alzheimer disease without concomitant atherosclerotic cardiovascular disease. Key messages: Heterogenous etiology of dementia, which in old age is usually a clinical diagnosis, may confound the role of long-term risk factors. In a longitudinal study with autopsy records, midlife cholesterol predicted dementia with features of atherosclerotic cardiovascular disease but not "pure" Alzheimer disease Glucose tolerance in midlife was not associated with pure Alzheimer's disease.